Could prolactin receptor gene polymorphism play a role in pathogenesis of breast carcinoma? - GÜLLÜOĞLU, MAHMUT BAHADIR (LIBRAPHARM, 2004)
Objective: Constitutive activation of various hormone and growth factor receptors is newly recognised as a common cause of tumour development. This study investigated the presence of any mutation or polymorphism of prolactin receptor (PRLR) in 38 patients with breast cancer. Research methods: Genomic DNA was extracted and PCR amplification was carried out for exon 1-10 of PRLR from tumoral and adjacent non-cancerous breast tissue of tumour specimens from 38 breast cancer patients. PCR products were analysed by SSCP and automatic sequencing for mutations. Results: For the first time, A150C (Leu-->Ile) transversion at exon 6 of PRLR in tumour tissues, in adjacent non-cancerous breast tissues, and in blood samples of two (5.3%) out of 38 patients with breast cancer were detected. In contrast to this finding, no polymorphism of PRLR in blood samples of 100 normal individuals were found. Conclusion: Polymorphism of prolactin receptors might play a role in mammary carcinogenesis as a consequence of intracellular changes of PRLR signalling.
Keywords: breast cancer; gene polymorphism; mammary carcinogenesis; prolactin receptors; receptors; GROWTH-HORMONE RECEPTOR; PRL RECEPTOR; CLINICAL-IMPLICATIONS; CANCER; ACTIVATION; TUMORS; EXPRESSION; INDUCTION; PATHWAYS; MAMMARY